Current and future perspectives of carbon and graphene quantum dots: From synthesis to strategy for building optoelectronic and energy devices. (January 2021) - Ghosh, Dibyendu; Sarkar, Krishnendu; Devi, Pooja; Kim, Ki-Hyun; Kumar, Praveen
Abstract: Carbon quantum dots (CQDs) and graphene quantum dots (GQDs) are new carbon-based nanomaterials with unique electronic, optical, and physicochemical properties. Both CQDs and GQDs have received attention in different material research fields such as optoelectronics, energy harvesting, chemical sensing, and biosensing. The combination of edge effects and/or zero-dimensional quantum-confined structures make them a promising alternative for applications like LED emitters, photodetectors, solar cells, water splitting, and optoelectronic devices. Despite the great potential for using these materials in energy harvesters, their potential in energy applications has not yet been reviewed thoroughly. In this review, we particularly focused on the role of edge effects and attached functional groups on flexible optoelectronic devices for energy harvesting applications. In addition, we also discussed the underlying challenges and future prospects for CQD/GQD-based devices with respect to their performance, sustainability, durability, and cost-effectiveness to efficiently realize their industrial scale-up. Highlights: The potential of carbon (CQD)/graphene quantum dots (GQD) is recognized for energy field. Here the material properties of CQDs/GQDs are assessed as energy harvesting devices. The advantages of CQDs/GQDs over the pre-existing materials are evaluated in various. The CQDs/GQDs have potential to be used for futuristic large-scale device applications. With.